Bioprocessing of oncolytic group B adenovirus for scalable production - Cooper, L (2014)
The central aim of this thesis was to develop strategies to improve the manufacture of the group B chimeric oncolytic adenovirus, ColoAd1, which rapidly kills and lyses host cells. In attempting to improve the cellular yield of ColoAd1, this thesis therefore sought to identify host infection-related factors that limited ColoAd1 production. In the widely-used manufacturing cell line, HEK293, ColoAd1 replication depleted intracellular ATP earlier than Ad11p and activated the intracellular energy sensor, AMPK. This might have reflected earlier ATP depletion, or possibly the absence of the E4orf4 protein from ColoAd1 compared to Ad11p. Despite this difference in AMPK activation, both viruses appeared able to maintain mTORC1 activity, which may be essential particularly for protein synthesis in the early stages of virus infection. For production purposes, preventing intracellular ATP depletion was seen as an attractive mechanism of maintaining ColoAd1 infected host cell viability and was hypothesised to lead to increased virus yield. A range of strategies were explored to enhance depleting ATP levels. Even though none of these were dramatically successful, they indicated that perhaps the anabolic building blocks required for viral replication were more important than cellular energy levels. Finally, a screening methodology based on siRNA knockdown was used to identify kinases that affected ColoAd1 replication. Many hits were identified, and several candidate kinases indicated a role for intracellular calcium signalling limiting virus particle production. Overall, data presented in this thesis supports the manufacture of ColoAd1 in HEK293 cells and suggest that enhancing glycolysis may increase ColoAd1 yield. It also provides mechanistic insights into the replication of ColoAd1 and Ad11p that may inform the improved design of group B oncolytic adenoviruses.